The Classical Greek Mercenary and his Relationship to the Greek Polis - Trundle, Matthew F. (My University, 1996)
This dissertation examines the role of the Greek mercenary in the history of the Greek city-states from the Dark-Ages down to the end of the Lamian War in 322 B.C. It does not address the strategic and tactical uses of mercenaries on the battlefields of the eastern Mediterranean, but illustrates the social, political, and economic positions of mercenaries both inside and outside of the polis. The principal purpose of this work has been to demonstrate the central role of mercenary service to Greek society and history. This role is demonstrated in the accepted nature of mercenary service among Greek citizens. Greek mercenaries came from all the regions of the Greek world and from all strata of Greek society. Mercenary service was important in forging links between individuals and communities apodemia and, as such, it was a means by which foreigners and foreign rulers could exercise their power and their influence over the Greeks.
Historians have studied the military uses of mercenaries. They have also studied specific aspects of mercenary service, such as pay, or specific regions and campaigns in which they served. Never before has one work examined mercenary service as a socio-economic problem for the whole polis period.
The sources for this work come from every type of Greek literature. Historians such as Thucydides and Xenophon have provided the narrative and military contexts for the adventures of mercenaries. Philosophers have illustrated attitudes towards military service overseas as well as the status at home. Technical writers, for example the fourth-century strategist Aeneas Tacticus, have provided information on a variety of important issues concerning mercenaries. Forensic speech writers have illustrated how ordinary men served at home and abroad with alacrity and seemingly without care, while political speeches have shown the concern with which some saw the growth in the numbers of Greeks abroad. As well as the literary sources, the coinage of the period has promoted an understanding of payment and the relationships between the employer and those in service.
By looking at Greeks who left the polis to serve abroad, either for a short campaign or for their entire lives, a clearer insight into the history of the city-states is achieved. In this study the focus of Greek history shifts from the inclusive communities of the Greek mainland to the tyrants and kings of the Mediterranean and the Near East. The Hellenistic world which emerged after Alexander, (and therefore beyond the scope of this thesis), embraced this wide geographic arena. In their work the Greek mercenaries of the polis period exemplify the continuity of one time frame to the next. The mercenaries aided the synthesis of east with west and as a result they laid the foundations for the world of the Hellenistic monarchies.
Keywords: ancient; history; Greek; polis; Arts and Humanities; History; History of Art, Architecture, and Archaeology; Philosophy; Arts and Humanities